2011
DOI: 10.1007/s13595-011-0122-y
|View full text |Cite
|
Sign up to set email alerts
|

Carbon in heartwood, sapwood and bark along the stem profile in three Mediterranean Pinus species

Abstract: Context: Understanding biological processes in forests is necessary to orientate ecosystem management towards potential C sequestration. To achieve this, information is required about changes in forest biomass C pools, including the stem components (bark, sapwood and heartwood).Aims: This study aimed to determine whether there are differences in C concentration in axial and radial directions within stem biomass in Pinus nigra, Pinus pinaster and Pinus sylvestris.Methods: Wood samples from a permanent plantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 17 publications
6
15
2
1
Order By: Relevance
“…Although the best solution for biomass estimation is difficult to establish, different alternatives should be explored that improve estimations (Weiskittel et al, 2015) and that incorporate: (1) consistency in biomass data gathering across large geographical scales, (2) generation of open datasets compiling volume, biomass, carbon and wood density data, (3) use of such open datasets to evaluate and compare biomass models, (4) testing of new model forms using data from technology such as airborne and terrestrial LiDAR and (5) the application of appropriate available mathematical and statistical methods. Another source of uncertainty stems from the use of general default values for forest species when specific differences in gravity and carbon contents are widely-known (Herrero et al, 2011, Castaño and Specific differences can even occur between tissues for each species, as Herrero et al (2011) determined for three Mediterranean pines (Pinus nigra Arn., Pinus pinaster Ait. and Pinus sylvestris L.) and Castaño and Bravo (2012) reported for two European oaks (Quercus petraea and Quercus pyrenaica Wild).…”
Section: Increasing Forest Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Although the best solution for biomass estimation is difficult to establish, different alternatives should be explored that improve estimations (Weiskittel et al, 2015) and that incorporate: (1) consistency in biomass data gathering across large geographical scales, (2) generation of open datasets compiling volume, biomass, carbon and wood density data, (3) use of such open datasets to evaluate and compare biomass models, (4) testing of new model forms using data from technology such as airborne and terrestrial LiDAR and (5) the application of appropriate available mathematical and statistical methods. Another source of uncertainty stems from the use of general default values for forest species when specific differences in gravity and carbon contents are widely-known (Herrero et al, 2011, Castaño and Specific differences can even occur between tissues for each species, as Herrero et al (2011) determined for three Mediterranean pines (Pinus nigra Arn., Pinus pinaster Ait. and Pinus sylvestris L.) and Castaño and Bravo (2012) reported for two European oaks (Quercus petraea and Quercus pyrenaica Wild).…”
Section: Increasing Forest Areamentioning
confidence: 99%
“…The three carbon storage compartments should be considered in all impact estimates. Carbon content in living biomass is easily estimated via species-specific equations or by applying factors to oven-dry biomass weights (e.g., Ibañez et al, 2002, Herrero et al, 2011, Castaño and Bravo, 2012. Litter carbon content has been analysed in many studies on primary forest productivity, though information regarding the influence of forest management on litter carbon content is less abundant (Blanco et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have shown that the carbon content can vary between species and between different fractions of biomass within the same species (Gifford 2000;FigueroaNavarro 2001;Gayoso and Guerra 2005;Avendaño et al 2009;Thomas and Martin 2012). In the case of Spain, data are available with regard to the carbon content of some forest tree species (Ibáñez et al 2002;Herrero et al 2011), but little information exists in relation to carbon content in shrub formations. Hence the importance of undertaking studies aimed not only at developing the necessary tools for estimating the amount of carbon sequestered by these formations but also at identifying options for their future commercial exploitation within a sustainable management system.…”
mentioning
confidence: 99%
“…Matthews 1993;Jina et al, 2008). Other authors believe that this value could introduce very large over-or under-estimates of carbon biomass into the calculation (Janssens et al, 1999;Herrero et al, 2011;Castaño & Bravo, 2012).…”
Section: Carbon Content In the Biomass Of Cork Oak Forestsmentioning
confidence: 99%